2020
DOI: 10.1007/s40801-020-00179-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adverse Events on the Progression-Free Survival of Patients with Advanced Hepatocellular Carcinoma Treated with Lenvatinib: A Multicenter Retrospective Study

Abstract: Background and Objective Experience of the use of lenvatinib (LEN) in the clinical setting remains limited. We conducted this study to elucidate the factors associated with progression-free survival (PFS) in patients with advanced HCC treated with LEN. Methods In this multicenter retrospective study, we analyzed data on patient characteristics, treatment outcomes, and adverse events (AEs) for 77 patients with advanced hepatocellular carcinoma (HCC). We also analyzed PFS and factors that influence PFS. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 26 publications
8
45
2
Order By: Relevance
“…The association of lenvatinib-induced hypothyroidism with clinical outcomes is controversial. Koizumi et al reported similar results [ 21 ] to ours, whereas Ohki et al, related this AE to poor survival [ 20 ]. Several studies analyzed the impact of therapy-induced hypothyroidism on prognosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The association of lenvatinib-induced hypothyroidism with clinical outcomes is controversial. Koizumi et al reported similar results [ 21 ] to ours, whereas Ohki et al, related this AE to poor survival [ 20 ]. Several studies analyzed the impact of therapy-induced hypothyroidism on prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…However, information on the association of AE occurrence with prognosis in lenvatinib therapy for HCC is limited. Ohki et al reported that lenvatinib-induced hypothyroidism of Grade ≥2 was an independent predictor of poorer PFS [ 20 ], whereas Koizumi et al, found that thyroid dysfunction was associated with better PFS [ 21 ]. Therefore, the impact of thyroid-related AE on prognosis is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Many real-world studies have reported the short-term therapeutic response of lenvatinib, resulting in an ORR of 29.9-53.5%, as assessed by mRECIST [17][18][19][20][21][22][23][24], and 14-25%, as assessed by RECIST ver.1.1 [19,22,25,26]. These findings seemed to be in agreement with the results of phase 2 and 3 studies (Table 1).…”
Section: Therapeutic Response Of Lenvatinib 21 the Ojective Responssupporting
confidence: 86%
“…We reported that BCLC intermediate stage was a significant predictive factor that was associated with the ORR in a multivariate analysis [18], which agreed with the results regarding the ORRs in the analysis of a Japanese subpopulation in the REFLECT trial [27]. A high ORR was found in patients with a good PS [21], Child-Pugh class A [21], and Child-Pugh score 5 (CP-5A) [23]. Some of the researchers also reported that the high relative dose intensity (RDI) at four weeks (30 days) [23,28,29] or eight weeks (60 days) [19,21,30,31] was relevant to therapeutic response of lenvatinib, including the PFS and OS ( Table 2).…”
Section: Therapeutic Response Of Lenvatinib 21 the Ojective Responssupporting
confidence: 83%
“…Another study reported that approximately 30% of patients had grade 3 or 4 AEs while undergoing treatment with LEN. They additionally reported that thyroid dysfunction and appetite loss during the administration of LEN were independent factors associated with shorter progression-free survival (PFS) [20]. We therefore considered that DLSAE was associated with poor prognosis in patients with HCC treated by LEN.…”
Section: Introductionmentioning
confidence: 99%